Museum Digitisations and Emerging Curatorial Agencies Online Vikings in the Digital Age - Axelsson, Bodil (Springer Nature, 2022)
This open access book explores the multiple forms of curatorial agencies that develop when museum collection digitisations, narratives and new research findings circulate online. Focusing on Viking Age objects, it tracks the effects of antagonistic debates on discussion forums and the consequences of search engines, personalisation, and machine learning on American-based online platforms. Furthermore, it considers eco-systemic processes comprising computation, rare-earth minerals, electrical currents and data centres and cables as novel forms of curatorial actions. Thus, it explores curatorial agency as social constructivist, semiotic, algorithmic, and material. This book is of interest to scholars and students in the fields of museum studies, cultural heritage and media studies. It also appeals to museum practitioners concerned with curatorial innovation at the intersection of humanist interpretations and new materialist and more-than-human frameworks.